The Epidemiology of Hepatitis C Virus in the Fertile Crescent: Systematic Review and Meta-Analysis. - Hiam Chemaitelly; Karima Chaabna; Laith J Abu-Raddad (PLoS ONE)
Objective To characterize hepatitis C virus (HCV) epidemiology in countries of the Fertile Crescent region of the Middle East and North Africa (MENA), namely Iraq, Jordan, Lebanon, Palestine, and Syria. Methods We systematically reviewed and synthesized available records of HCV incidence and prevalence following PRISMA guidelines. Meta-analyses were implemented using a DerSimonian-Laird random effects model with inverse weighting to estimate the country-specific HCV prevalence among the various at risk population groups. Results We identified eight HCV incidence and 240 HCV prevalence measures in the Fertile Crescent. HCV sero-conversion risk among hemodialysis patients was 9.2% in Jordan and 40.3% in Iraq, and ranged between 0% and 3.5% among other populations in Iraq over different follow-up times. Our meta-analyses estimated HCV prevalence among the general population at 0.2% in Iraq (range: 0-7.2%; 95% CI: 0.1-0.3%), 0.3% in Jordan (range: 0-2.0%; 95% CI: 0.1-0.5%), 0.2% in Lebanon (range: 0-3.4%; 95% CI: 0.1-0.3%), 0.2% in Palestine (range: 0-9.0%; 95% CI: 0.2-0.3%), and 0.4% in Syria (range: 0.3-0.9%; 95% CI: 0.4-0.5%). Among populations at high risk, HCV prevalence was estimated at 19.5% in Iraq (range: 0-67.3%; 95% CI: 14.9-24.5%), 37.0% in Jordan (range: 21-59.5%; 95% CI: 29.3-45.0%), 14.5% in Lebanon (range: 0-52.8%; 95% CI: 5.6-26.5%), and 47.4% in Syria (range: 21.0-75.0%; 95% CI: 32.5-62.5%). Genotypes 4 and 1 appear to be the dominant circulating strains. Conclusions HCV prevalence in the population at large appears to be below 1%, lower than that in other MENA sub-regions, and tending towards the lower end of the global range. However, there is evidence for ongoing HCV transmission within medical facilities and among people who inject drugs (PWID). Migration dynamics appear to have played a role in determining the circulating genotypes. HCV prevention efforts should be targeted, and focus on infection control in clinical settings and harm reduction among PWID.